Penerapan Operasi Hitung Bilangan Bulat Bernuansa Etnomatematika Melalui Media Wayang Singkong - Dhian Nuri Rahmawati; Dafid Slamet Setiana; Edi Subarkah; Pardimin Pardimin; Muhammad Irfan (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2022)
Ethnomathematics is the integration of cultural elements into mathematics learning. To foster a sense of love and preserve the cultural heritage of the past, the mathematical elements contained in the culture of the community need to be studied further. This study aims to identify and describe the application of ethnomathematical integer arithmetic operations through cassava puppet media in activating student learning activities and preserving traditional games. This research is a qualitative descriptive study. The subjects in this study were 10 students of class VI group B SD Rejosari Tanjungsari. The method of data collection in this research is the method of observation, interviews, and documentation. The results of this study are: the use of cassava puppet media in the addition and subtraction of integers goes according to expectations, namely student activities in learning show positive results. It also preserves traditional games by introducing wayang cassava as an entertainment medium as well as a learning medium.Keywords: arithmetic operations, integers, media, cassava puppets